Analyzing Regional Variation in Health Care Utilization Using (Rich) Household Microdata - Peter Eibich; Nicolas Ziebarth (Institute for the Study of Labor (IZA), 2013)
This paper exploits rich SOEP microdata to analyze state-level variation in health care utilization in Germany. Unlike most studies in the field of the Small Area Variation (SAV) literature, our approach allows us to net out a large array of individual-level and state-level factors that may contribute to the geographic variation in health care utilization. The raw data suggest that state-level hospitalization rates vary from 65 percent to 165 percent of the national mean. Ambulatory doctor visits range from 90 percent to 120 percent of the national mean. Interestingly, in the former GDR states doctor visit rates are significantly below the national mean, while hospitalization rates lie above the national mean. The significant state-level differences vanish once we control for individual-level socio-economic characteristics, the respondents' health status, their health behavior as well as supply-side state-level factors.
Keywords: I12; I14; I18; 330; small area variation; health care utilization; SOEP